2001
DOI: 10.1063/1.1344225
|View full text |Cite
|
Sign up to set email alerts
|

Interparticle coupling effects in nanofabricated substrates for surface-enhanced Raman scattering

Abstract: Surface-enhanced Raman scattering ͑SERS͒ substrates, consisting of arrays of electromagnetically coupled Ag nanoparticles on Si, were manufactured by electron-beam lithography. Substrate Raman efficiency, evaluated from the relative SERS intensities of the adsorbates rhodamine 6G and thiophenol, was found to increase rapidly with decreasing interparticle separation, signaling the importance of strong interparticle coupling effects in SERS. The observed SERS efficiency variation can be qualitatively explained i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
408
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 426 publications
(418 citation statements)
references
References 9 publications
8
408
2
Order By: Relevance
“…In contrast to earlier experimental and theoretical work that suggested that the SERS enhancement is largest for junctions with the smallest gap (10,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), here we find a non-zero optimum gap size for a specified excitation wavelength that results from the red-shifting of the dipole plasmon wavelength as gap size is decreased. Second, we show that there is also an optimum particle size that reflects the ability of light to penetrate into and be confined by the gap structure.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…In contrast to earlier experimental and theoretical work that suggested that the SERS enhancement is largest for junctions with the smallest gap (10,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), here we find a non-zero optimum gap size for a specified excitation wavelength that results from the red-shifting of the dipole plasmon wavelength as gap size is decreased. Second, we show that there is also an optimum particle size that reflects the ability of light to penetrate into and be confined by the gap structure.…”
Section: Resultscontrasting
confidence: 53%
“…Two mechanisms are often mentioned in the literature, (6) the electromagnetic mechanism and the chemical mechanism. The latter involves charge transfer excitation (7, 9) between analyte molecules and the metal particles, whereas the former is dominated by plasmon excitation leading to hot spots around nano-sized metal particles (10,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). A challenge in characterizing the electromagnetic mechanism is the difficulty associated with making nanoparticle structures with controllable interparticle gaps and doing so in a way that does not significantly change chemical composition.…”
mentioning
confidence: 99%
“…As reported, this structure is more approachable than the theoretical model that an analyte molecule positioned between two noble metal NPs can be enhanced greatly. 52 So one of the most interesting possibilities about the method of fabricating sandwich structures on glass is to achieve a kind of electromagnetic coupling effect between the two layers of metal NPs through controlling the assembly process, and this effect is known to give a dominant contribution to the SERS efficiency. 49 Therefore, large EF values are estimated to exist in such sandwich structure.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, electronbeam lithography substrates have been used to explore the magnitude of the enhancement factor while the interparticle spacing is varied; enhancement factors as large as 10 8 have been achieved (32,33). Immobilized colloidal nanoparticles have been used as a SERS substrate for the analysis of the eluent in the CE separation of small molecules, such as amino acids (34 ).…”
Section: Sers Substratesmentioning
confidence: 99%